Повышение достоверности результатов тестирования по математике в системе дистанционного обучения - Тиунчик, А. А.; Болтянская, Наталья Ивановна; Болтянська, Наталя Іванівна; Boltianska, Natalia (ТДАТУ, 2021)
RU : В статье рассмотрены вопросы повышения достоверности результатов тестирования по математике в системе дистанционного обучения. EN : The article discusses the issues of increasing the reliability of test results in mathematics in the distance learning system.
Increasing the reliability of testing results in mathematics in the distance learning system
Keywords: дистанционное обучение; информационное обеспечение; средства и методы контроля; distance learning; information support; means and methods of control